Pengaruh gaya kognitif FI-FD dan minat belajar terhadap pemahaman konsep matematika pada materi segitiga dan segiempat - Akhiroh, Mazro'atul; Zawawi, Irwani; Khikmiyah, Fatimatul (IKIP Siliwangi, 2023)
The purpose of this study was to determine whether the field dependent-field independent cognitive style and interest in learning partially or simultaneously affect the understanding of mathematical concepts. This type of research is a quantitative study with a population of all class VII SMP Muhammadiyah 4 Kebomas, namely as many as 57 students, a sample of 30 respondents was taken utilizing corresponding arbitrary inspecting strategy. Information assortment procedures are by survey and test. Information examination method utilizing various direct relapse investigation. In light of the aftereffects of the relapse test, the results show that: 1) There is a significant influence of cognitive style and interest in learning simultaneously on the understanding of mathematical concepts. 2) There is a significant influence of cognitive style on the understanding of mathematical concepts. 3) There is a massive impact of interest in learning on the understanding of mathematical concepts. Based on data analysis, it can be interpreted that field dependent-field independent cognitive style and interest in learning partially or simultaneously have a significant effect on the understanding of mathematical concepts.